THE IMPACT OF ENVIRONMENTAL EDUCATION CAMPAIGNS ON SOCIAL MEDIA: A STUDY OF THE DIGITAL COMMUNICATION STRATEGY OF INSTAGRAM ACCOUNT @BULE_SAMPAH - Sarah Wulandari; Rofi’ah; Yama Pradana Sumbodo (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The waste problem in Indonesia continues to increase as public awareness of environmental management is low. Plastic waste, in particular, has a serious impact on ecosystems and human health. Handling the environment requires not only a technical approach, but also a change in people’s mindset and behavior. In this context, social media is utilized as a campaign tool to build public ecological awareness. This study aims to determine the impact of the environmental education campaign carried out by the Instagram account @bule_sampah through content with communication strategies on social media which is an effective means of delivering environmental education and has a real impact on the audience. This campaign is packaged in the form of visuals, informative narratives, and collaborative invitations that aim to build awareness and encourage changes in people’s behavior towards environmental issues. Using a descriptive qualitative approach and the AIDA model as an analytical framework, this study found that the @bule_sampah account consistently utilizes visual content, educational narratives, and active interaction to attract attention, build interest, and encourage real action from the audience in waste management.